Moderating Effect of Innovation on the Relationship of Supply Chain Management Practices and Firm Performance: A Study of SMEs - Phutthiwat Waiyawuththanapoom; Pimploi Tirastittam; Sittichai Pintuma; Wissawa Aunyawong (International Journal of Supply Chain Management, 2020)
The study examines the moderating effect of innovation in the relationship of supply chain management practices (SCMP) and firm performance (FP) of the SMEs of Indonesia.  To achieve this objective, using cross sectional research design, 250 questionnaires were distributed among the supply chain managers of the SMEs by using a convenient sampling technique which yield an 80% response rate. The data was analyzed by using the Structural Equation Modeling (SEM) technique. The findings of the study have shown that all the management practices have a positive and significant relationship with the FP of Indonesia SMEs. Furthermore, indirect moderating effect of innovation also shown that Innovation has a positive and significant moderating effect in most of the SCMP and FP. Whereas, one of the SCMP namely, quality information sharing (QIS) and FP relationship is not significantly moderated by the innovation. These findings empirically revealed that innovation is considered to be a significant moderator in the relationship of SCMP and FP which is considered to be significant contribution in the current study. Therefore, the current study added a body of literature in the existing empirical findings. The research limitation and future directions are also discussed at the last of the study.